Proposal for the Ericiolaceae (Prymnesiophyceae, Haptophyta) fam. nov. - Archontikis, OA; Thomsen, HA; Meier, KJS; Young, JR (International Nannoplankton Association, 2024)
The extant nannolith-bearing genera Ericiolus and Pileolosphaera are distinguished by the possession of triradiate nannoliths with a very similar and highly distinctive structural pattern. The nannoliths display three symmetrically arranged rays that develop from a nannolith center but show no obvious affinities to any other currently known extant coccolithophore. On this basis, we propose the establishment of a new family, Ericiolaceae fam. nov., to accommodate Ericiolus and Pileolosphaera.